Analisis Perilaku Mahasiswa Sains dan Teknologi dalam Penggunaan Smartphone (gadget) untuk Meningkatkan Prestasi Akademik - Ekie Gilang Permata; Harpito Harpito; Ismu Kusumanto; Zulmiriyanto Zulmiriyanto (JURNAL TEKNIK INDUSTRI, 2019)
Nowadays smartphone users are increasing, including Industrial Engineering Students at UIN SUSKA Riau. The use of smartphones has a positive-negative impact so it is worth responding to as best as possible. Student behavior using smartphones varies, whether it is in line with expectations to improve academic achievement. Research knows how the behavior of students using smartphones with statistical tests, namely the test of validity, reliability and linear regression test to determine the effect of independent variables on the dependent variable (Student IP). Based on the results of the study involving 260 samples from 737 population of Industrial Engineering Students in 2018 showed a reliability value of 0.746 with 25 statements declared valid. The results of linear regression are Y=2,796+0,004X1-0,029X2+0,019X3+0,089X4+0,051X5+0,033X6+0,051X7. The most influential variable is the variable "content that is accessed", meaning that if the content is accessed can be increased it can improve academic achievement. The negative value is the variable "Asking the Lecturer with social media", meaning that asking a lot of lecturers with social media is not recommended especially personal matters because of the lecturer guiding. Thus the behavior of students using smartphones influences academic achievement.